2019
DOI: 10.1002/nsg.12072
|View full text |Cite
|
Sign up to set email alerts
|

Induced polarization applied to biogeophysics: recent advances and future prospects

Abstract: This paper provides an update on the fast‐evolving field of the induced polarization method applied to biogeophysics. It emphasizes recent advances in the understanding of the induced polarization signals stemming from biological materials and their activity, points out new developments and applications, and identifies existing knowledge gaps. The focus of this review is on the application of induced polarization to study living organisms: soil microorganisms and plants (both roots and stems). We first discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 181 publications
(426 reference statements)
0
53
0
Order By: Relevance
“…Understanding of the root–soil–fluid interface from an electrochemical point of view and the inner root ionic distribution is necessary to properly interpret the overall signature when an external field is applied. More EIS and SIP studies at the root scale will help to improve the understanding of the main underlying mechanisms of polarization in roots, which is a requirement for the development of a phytophysical model (Kessouri et al., 2019) that links root electrical signatures to root properties and root activity.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding of the root–soil–fluid interface from an electrochemical point of view and the inner root ionic distribution is necessary to properly interpret the overall signature when an external field is applied. More EIS and SIP studies at the root scale will help to improve the understanding of the main underlying mechanisms of polarization in roots, which is a requirement for the development of a phytophysical model (Kessouri et al., 2019) that links root electrical signatures to root properties and root activity.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 99%
“…It uses a broad range of frequencies from millihertz to tens of kilohertz and four electrodes to reduce the influence of contact resistances and to improve the accuracy of the complex impedance measurements (Zimmerman et al 2008). Spectral induced polarization has been successfully applied in various biogeophysical investigations (Abdel Aal, Atekwana, Slater, & Atekwana, 2004;Abdel Aal, Slater, & Atekwana, 2006;Atekwana & Slater, 2009;Atekwana, Werkema, & Atekwana, 2006;Kessouri et al, 2019). Mary et al (2017) studied isolated coarse roots (in the laboratory) and found that coarse roots showed higher resistivity and polarized differently compared with soil, suggesting that SIP is a promising tool for root studies.…”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…; Kessouri et al . ). In biochar containing media, geophysical methods can be used to characterize biochar concentration and/or monitor biochar‐related processes.…”
Section: Introductionmentioning
confidence: 97%